2016
DOI: 10.1186/s13068-015-0423-8
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic evaluation of integrated first- and second-generation ethanol production from grain and straw

Abstract: BackgroundIntegration of first- and second-generation ethanol production can facilitate the introduction of second-generation lignocellulosic ethanol production. Consolidation of the second-generation with the first-generation process can potentially reduce the downstream processing cost for the second-generation process as well as providing the first-generation process with energy. This study presents novel experimental results from integrated first- and second-generation ethanol production from grain and whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
346
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(377 citation statements)
references
References 40 publications
19
346
0
7
Order By: Relevance
“…Analyzing the cell pellets and supernatant separately showed that 97% of the produced fatty alcohol was associated with or trapped in the cells while only 3% was secreted (Table 2). This result is consistent with the recent research about Y. lipolytica that most of the fatty alcohols were retained intracellularly when TaFAR1 gene was expressed in Y. lipolytica [31]. Using a 10% (v/v) dodecane overlay during growth, 92.5% of the produced fatty alcohols were extracted into the dodecane phase, while only 5% remained associated with cells (Table 2).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Analyzing the cell pellets and supernatant separately showed that 97% of the produced fatty alcohol was associated with or trapped in the cells while only 3% was secreted (Table 2). This result is consistent with the recent research about Y. lipolytica that most of the fatty alcohols were retained intracellularly when TaFAR1 gene was expressed in Y. lipolytica [31]. Using a 10% (v/v) dodecane overlay during growth, 92.5% of the produced fatty alcohols were extracted into the dodecane phase, while only 5% remained associated with cells (Table 2).…”
Section: Resultssupporting
confidence: 91%
“…In addition to the “pull” strategy, blocking TAG synthesis, i.e., disruption of the dga gene which encodes for diacylglycerol acyltransferase, the final enzyme for TAG synthesis, is another strategy for further enhancing fatty alcohol production. Also, as demonstrated in recent research [31], eliminating fatty alcohol degradation pathway, might be another strategy deserving a try. However, considering the complex nature of this species and for other unknown genetic reasons, the subsequent knocking out genes is very challenging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition the production of ethanol from agricultural wastes (e.g. straw, bagasse) gains more importance (Sarkar et al, 2012;Joelsson et al, 2016).…”
Section: Ethanolmentioning
confidence: 99%
“…When production occurs from easily accessible sugars, it is referred to as first generation (1G) production, whereas, if lignocellulosic materials such as agricultural residues, forest materials and dedicated crops are used, they are called second-generation (2G) production (Joelsson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%